Adaptive backstepping approach for dc‐side controllers of Z‐source inverters in grid‐tied PV system applications. Issue 14 (23rd October 2018) - Vu, Phuong; Nguyen, Quan; Tran, Minh; Todeschini, Grazia; Santoso, Surya
Abstract : Z ‐source inverters (ZSIs) are single‐stage power converters with both voltage buck and boost capabilities provided by the unique impedance network and the ability to operate during shoot‐through states. This study proposes a novel non‐linear adaptive backstepping method for dc‐side controllers in a multi‐loop control scheme of the ZSI in grid‐tied photovoltaic (PV) systems. Despite the variability of the capacitor and inductor values in the ZSI impedance network, the proposed controller guarantees robust and stable operation under varying levels of PV irradiance and temperature. The shoot‐through duty ratio of the ZSI is obtained directly from the output of an MPPT algorithm and the measured PV and inductor currents. This strategy overcomes the disadvantages of the conventional approach such as the non‐minimum phase at the dc side of the ZSI. It also eliminates the need to linearise the voltage/current characteristics of the PV arrays and ZSI model. The ac‐side controllers consist of an outer proportional–integral voltage controller and an inner deadbeat current controller to achieve unity power factor and stable capacitor voltage in spite of grid voltage fluctuations. The efficacy of the proposed adaptive backstepping controller and the multi‐loop control scheme is validated by offline and hardware‐in‐the‐loop real‐time simulations.